2020
DOI: 10.1111/jfbc.13214
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity effects of the combination ofPatrinia scabiosaefoliaroot andHippophae rhamnoidesleaf extracts

Abstract: Patrinia scabiosaefolia (PS) and Hippophae rhamnoides (HR) are traditionally used functional foods. Extracts from the root of PS are known for their anti-inflammatory effects, whereas those from the leaf of HR are effective at both preventing and treating obesity. This study investigated whether the extract combination of PS and HR (PHE) affected weight loss in obese mice. In vitro experiments demonstrated that PHE showed a synergistic effect on inhibiting adipocyte differentiation as compared with treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Combined treatment with extracts from these two plant species could have a synergistic effect. Choi et al showed that Patrinia scabiosaefolia and Hippophae rhamnoides extracts had a synergistic anti-obesity effect [19]. Similarly, crocin, chlorogenic acid, geniposide, and quercetin have been shown to reduce lipid accumulation in hepatic cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…Combined treatment with extracts from these two plant species could have a synergistic effect. Choi et al showed that Patrinia scabiosaefolia and Hippophae rhamnoides extracts had a synergistic anti-obesity effect [19]. Similarly, crocin, chlorogenic acid, geniposide, and quercetin have been shown to reduce lipid accumulation in hepatic cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…The main components of TFH is isorhamnetin, and the purity is more than 95%. The concentration of TFH solution [dissolved in Dimethyl sulfoxide (DMSO)] used in this study was 10, 20, and 50 μg/ml ( 8 , 9 ). Other chemical regents used in this study were obtained from Sigma-Aldrich Merck (Sigma-Aldrich, St. Louis, MO, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid extraction from the liver was performed based on the Folch method (Folch et al, 1957). Liver samples were homogenized in 0.9% NaCl and incubated overnight at 4 °C in a 20‐fold volume of the chloroform‐methanol mixture (2:1, v/v) (Choi et al, 2020). Chloroform‐soaked filter paper (No.…”
Section: Methodsmentioning
confidence: 99%